2020
DOI: 10.3390/ijerph17124538
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Evaluation of a Digital Intervention to Improve Sedentary Behaviour Across Multiple Workplace Settings

Abstract: Background: Prolonged sedentary behaviour (SB) is associated with risk of chronic diseases. Digital interventions in SB require mixed method evaluations to understand potential for impact in real-world settings. In this study, the RE-AIM QuEST evaluation framework will be used to understand the potential of a digital health promotion application which targets reducing and breaking up SB across multiple workplace settings. Methods: Four companies and 80 employees were recruited to use a digital application. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…The process evaluation should be reported to provide important information about how to replicate the intervention and what generalisable knowledge can be drawn from the implementation [ 26 , 27 ]. Encouragingly, there have been several recent sit less studies published which have reported intervention development or implementation processes [ 54 , 55 , 56 , 57 ]. Finally, future research could consider contextual factors that may present as competing priorities and could consider focusing on how to alter organisational culture by challenging the social norms of workplace sitting in order to successfully implement such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The process evaluation should be reported to provide important information about how to replicate the intervention and what generalisable knowledge can be drawn from the implementation [ 26 , 27 ]. Encouragingly, there have been several recent sit less studies published which have reported intervention development or implementation processes [ 54 , 55 , 56 , 57 ]. Finally, future research could consider contextual factors that may present as competing priorities and could consider focusing on how to alter organisational culture by challenging the social norms of workplace sitting in order to successfully implement such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…[38] evaluated the role of age and gender in consumer intentions and uptakes of mobile banking services. MacDonald et al [39] focused on the potential of a digital health promotion application directed on decreasing sedentary behaviors across multiple workplace settings. A study by Powell et al [40] explored the value that apps are currently generating and being reimbursed across the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prompting frequent short PA breaks may be one effective way to increase PA and reduce sedentary behavior ( 35 ). Research on digital media as transmitters of nudges has revealed first insights on positive effects of low-threshold interventions, such as daily emails or on-screen break prompting systems ( 36 – 38 ) as well as digital personalized applications with exercises, and advanced information ( 39 , 40 ). These insights showed for example that people adhere to the email or SMS message encouragements for daily stair-walks at work ( 36 , 41 , 42 ), or for health enhancing website use ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…These insights showed for example that people adhere to the email or SMS message encouragements for daily stair-walks at work ( 36 , 41 , 42 ), or for health enhancing website use ( 37 ). They also adhere to digital application for break up sedentary behavior at workplaces ( 40 ). Other findings revealed that nudging can be improved via personalization like individual preferences or the option to sync prompts with online calendars ( 39 ).…”
Section: Introductionmentioning
confidence: 99%